Second harmonic generation and ferromagnetic resonance of BaTiO3–BiFeO3 films and nanorod arrays - Nicholas W G Smith; Rathsara R H H Mudiyanselage; Shuang Wu; Satoru Emori; Brenden A Magill; Shashank Priya; Giti A Khodaparast (JPhys Materials)
The solid solution of BaTiO _3 –BiFeO _3 (BTO–BFO) exhibits enhanced magneto-electric coupling compared to the widely explored BiFeO _3 . In this study, we examined BTO–BFO nanorod arrays (and films) ranging from 200 to 600 nm in height (and thickness) by employing second harmonic emission (SHE) and ferromagnetic resonance (FMR) measurements. We demonstrated a large enhancement in SHE in nanorod arrays compared to the films, which can be attributed to the high surface-to-volume ratio in the nanorod arrays. Our FMR measurements showed low effective damping parameters of (4–8) $×$ 10 ^−3 in both nanorods and film structures. These observations are promising for future nonlinear optoelectronics and spintronics applications.